Isobavachalcone Activates Antitumor Immunity on Orthotopic Pancreatic Cancer Model: A Screening and Validation - Liu, Xuanming; Zhang, Hongbo; Cao, Jianlin; Zhuo, Yuzhen; Jin, Jiahui; Gao, Qiaoying; Yuan, Xiangfei; Yang, Lei; Li, Dihua; Wang, Yan (Frontiers in Pharmacology, 2022)
Pancreatic cancer accompanies poor prognosis and accounts for a significant number of deaths every year. Due to possessing a broad spectrum of bioactivities such as antioxidant and antitumor activity, Psoralea corylifolia L. (PCL) is widely used in clinical Chinese medicine. In the present work, we explored potential antitumor agents of PCL and underlying mechanisms in vivo and vitro experiments. Based on the integration of network pharmacology, protein-protein interaction network, the expression profile of gene, survival analysis, multivariate Cox regression model, and molecular docking, we considered Isobavachalcone (IBC) as a candidate compound. Subsequently, we confirmed that IBC could inhibit Panc 02 cells proliferation and induce apoptosis via increasing ROS production in vitro. Meanwhile, IBC could attenuate the weight of orthotopic pancreatic cancer in mice, increase CD8+ cells and reduce M2 macrophages polarization in the tumor tissue and spleen. IBC also alleviated the proportion of MDSCs in the tumor tissue but had no change in the spleen. In addition, IBC restrained the polarization of RAW 264.7 cells into M2 macrophages by inhibiting the expression of ARG1 and MRC1 and suppressed the expression of ARG1 and TGF-β in BM-derived MDSCs. Thus, IBC can attenuate orthotopic pancreatic cancer growth via activating immune activity and inducing cell apoptosis. This research could be a reference for the antitumor ability of IBC and the treatment of the immunosuppressive tumor microenvironment in pancreatic cancer.